Back Cover: Carbohydrate Self‐Assembly at Surfaces: STM Imaging of Sucrose Conformation and Ordering on Cu(100) (Angew. Chem. Int. Ed. 25/2019). Issue 25 (28th May 2019) - Abb, Sabine; Tarrat, Nathalie; Cortés, Juan; Andriyevsky, Bohdan; Harnau, Ludger; Schön, J. Christian; Rauschenbach, Stephan; Kern, Klaus
Abstract : Sweet surface Employing electrospray ion beam deposition, nonvolatile sucrose can be deposited on clean surfaces. In their Communication on page 8336 ff., S. Abb et al. present the 2D crystalline assembly of sucrose on a Cu(100) surface. By combining scanning tunneling microscopy images and multi‐stage modelling, the conformation and assembly pattern of sucrose is revealed.